PROSES PENEGAKAN HUKUM TERHADAP PELANGGARAN TINDAK PIDANA RINGAN KAITANNYA DENGAN PERMA No. 02 TAHUN 2012 TENTANG PENYESUAIAN BATASAN TINDAK PIDANA RINGAN DAN JUMLAH DENDA DALAM KUHP - Mansur Mansur (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT There are several factors contributing to the misdemeanor in Indonesia, namely economic factors, sosilogi, and psychology, the third fakror has a close relationship with each other to bring about a misdemeanor, meaning that one of the factors that are influenced by other factors so that one factor can not be stand alone in causing trouble misdemeanor.The function of the criminal procedure law is to implement and enforce. Criminal Law. This function can be considered as a function repressit criminal law, meaning that if the act is classified as a criminal act, then such actions must be processed so that the provisions contained in the criminal law can be applied to the perpetrators: Police; Attorney and District Court. Implementation of the law was to be touched not only the man who is being tried for violations of the law, but also touching the victim of crime, and the legal officers of police, prosecutors, judges and corrections officials, and ultimately the entire nation. Law enforcement officers are human beings, as well as law offenders are people too, so that the criminal law is formal and material dealing with human beings who desire a bright tomorrow and serene.